The Clinical Threshold for Treatment in Psychiatry - Giovanni A. Fava; Jenny Guidi (JAMA Psychiatry, 2026)
This Viewpoint highlights the determinants of treatment thresholds that should be considered for psychiatric care and explores the implications of recent developments in clinimetrics in this field.